Infrastructure, Human Capital, And Local Revenue As Determinants of Economic Growth in North Maluku Province - Liong Finox Konu; Teddy Ch. Leasiwal; Jopie Tamtelahitu (LP2M IAIN Palopo, 2026)
North Maluku Province has recorded positive economic growth in recent years; however, this progress has been accompanied by substantial regional disparities in development across regencies/cities. These regional disparities are reflected in unequal infrastructure provision, variations in the quality of human capital, and uneven contributions of Local Own-Source Revenue (Pendapatan Asli Daerah, PAD), all of which constrain the acceleration of inclusive regional economic growth. This study aims to examine the effects of infrastructure, human capital, and PAD on economic growth in North Maluku Province. This quantitative study utilized panel data from 10 regencies/cities over the period of 2021-2024. The data was analyzed using panel data regression analysis with a Fixed Effect Model. The findings indicate that infrastructure, human capital, and PAD each have a positive and statistically significant effect on economic growth in North Maluku Province. Nevertheless, the magnitude of these effects varies considerably across regions. Areas with a strong mining base and relatively well-developed infrastructure exhibit higher contributions to economic growth compared to regions that rely primarily on trade and agriculture and are characterized by lower human capital quality. Based on these results, this study recommends the implementation of integrated and equitable development policies, including more targeted infrastructure investment, improved access to and quality of education to strengthen human capital, and the optimization of local economic potential to enhance PAD. Such measures are essential to promote more inclusive and balanced economic growth across all regions of North Maluku Province.